Twórczość Bogdana Czaykowskiego w kręgu Oficyny Poetów i Malarzy - Szałasta-Rogowska, Bożena (Tematy i Konteksty, 2024)
The article concerns the problem of cooperation between Bogdan Czaykowski and Poets’ and Painters’ Press. This cooperation was not permanent and regular, but it lasted with breaks for fourteen years - from 1957 to 1971. During this time, Czaykowski published two volumes of poetry at OPiM - his debut titled Trzciny czcionek in 1957 and the poem Sura. Wiersze in 1961. From 1967, he also published his poems (21 works in total), translations of poems from English into Polish (5 works by Michael Bullok) and critical literary sketches (one in Polish about the work of Tadeusz Peiper and two in English devoted to poetry by Leopold Staff and Czesław Miłosz). "Oficyna Poetów" also published three translations into English of Bogdan Czaykowski's poems by Adam Czerniawski, and the fifth of Jan Brzękowski's essays from the series Rozmowa z sobowtórem, published in the magazine, is devoted to Czaykowski's achievements. The article proves that the poet's cooperation with Krystyna and Czesław Bednarczyk was mutually beneficial.